A unique polygenic mouse model of obesity exhibits a distinct immunological profile that may offer protection against systemic inflammation, diabetes, and behavioral impairments - Gimsa, Ulrike; Koczan, Dirk; Kanitz, Ellen; Tuchscherer, Armin; Rebl, Alexander (Frontiers in Immunology, 2025)
In both humans and mice, obesity is often associated with peripheral and central inflammation, which can lead to diabetes, dysregulation of the stress response, changes in affective behavior, and memory impairment. The DU6 polygenic mouse line was selected over more than 180 generations for a high body mass. Unlike other mouse lines, DU6 mice do not develop diabetes despite significant obesity. We performed a series of behavioral tests on male mice because obesity is often associated with cognitive and emotional impairment. DU6 mice showed no differences in spatial memory or anxiety compared to a control mouse line, based on performance in the Y-maze test, novel object recognition task, and elevated plus-maze test, whereas object memory was impaired in DU6 mice. After psychological stress evoked by the elevated plus-maze test, serum corticosterone concentrations were elevated only in the control mouse line, while corticosterone concentrations were already high in DU6 mice under non-stressed conditions. This elevation under control conditions was no longer detectable at an advanced age. We investigated the composition of immune cells in the spleen and assessed mitogen-induced T-cell activation in vitro in male DU6 mice. Compared to the control mouse line, DU6 mice exhibited significantly fewer CD4+ and CD8+ T cells, alongside a markedly higher proportion of macrophages and Gr-1+CD11b+ myeloid-derived suppressor cells. T-cell activation following mitogen stimulation was lower in DU6 mice than in the control mouse line. Following psychological stress induced by the elevated plus-maze test, the number of CD4+ T cells increased and the number of macrophages decreased in both mouse lines. The proinflammatory cytokines IL-1β, IL-6, and TNF-α were not detectable in the serum of male mice of both lines, ruling out systemic inflammation. Transcriptomic analysis also revealed no inflammation in the hippocampal tissue, but rather a distinct transcriptional signature in male DU6 mice compared to the controls. We propose that the high number of Gr-1+CD11b+ cells protects DU6 mice against systemic inflammation, diabetes, and behavioral impairment.